An Experimental Method of Distribution Behavior of Hydrophobically Associated Polymer AP-P4 in Three-Phase Systems - Ruyin Li; Guorong Tan; Jian Zhang (Journal of Chemistry)
A novel experimental method has been established for the first time to evaluate the distribution behavior of water soluble hydrophobically associated polymer AP-P4 in the oil-water-solid three-phase systems, based on the static adsorption principle. Suitable analysis method has been selected to measure the concentration of polymer in every phase. The enrichment of polymer has been observed between the oil-aqueous interlayer. The distribution coefficient of AP-P4 is obtained along with the variation of concentration and total salinity. The experimental method is helpful to reveal the property of polymer solution and has potential usage in predicting the adsorption and retention in polymer flooding and the wastewater dealing of polymer flooding.